Scandcleft randomised trials of primary surgery for unilateral cleft lip and palate: 2. Surgical results. Issue 1 (2nd January 2017) - Rautio, Jorma; Andersen, Mikael; Bolund, Stig; Hukki, Jyri; Vindenes, Hallvard; Davenport, Peter; Arctander, Kjartan; Larson, Ola; Berggren, Anders; Åbyholm, Frank; Whitby, David; Leonard, Alan; et al.
Abstract: Background: Longstanding uncertainty surrounds the selection of surgical protocols for unilateral cleft lip and palate, and randomised trials have only rarely been performed. The Scandcleft Project consists of three trials commenced in 1997 involving ten centres in Denmark, Finland, Norway, Sweden, and the UK. Three groups of centres tested a newly-defined common technique for palatal repair (Arm A) against their local protocols (Arms B, C, D). Arm A was familiar to most of the surgeons in Trial 1, but not to the surgeons in the other Trials. Aim: To evaluate surgical events and complications of the 448 (293 boys, 155 girls) patients with complete unilateral cleft lip and palate (UCLP) enrolled in the three trials. Method: The three trials were carried out in parallel in adherence with a fully developed, ethically approved protocol. Operative time, bleeding, complications, and major dehiscence during and after both primary surgeries were recorded by the surgeon. Rates of fistula and surgery for velopharyngeal incompetence (VPI) were assessed until the youngest patient of the study had reached the age of 9 years. Pearson Chi-square statistical analysis was used to compare the outcomes. Results: No significant differences in bleeding, infection, anaesthetic complications or length of hospital stay between the different arms were found for Trial 1. However, in Trials 2 and 3 there were more airway problems in Arm A than with the traditional local protocols (Arms C or D). In Trial 3 fistula and VPI surgery rates were also higher in Arm A. Conclusions: The results do not provide statistical evidence that any technique is better than others, but indicate that surgery was more problematic for surgeons who were still gaining experience with an unfamiliar surgical protocol. Trial registration: ISRCTN29932826.